Zonulin and copeptin relation to some metabolic markers in school-aged obese children - Sahar Abd El-Ra; Rehab A. Mahmoud; Nayera E Hassan; Manal M. Aly; Hanaa Reyad Abdallah; Sherin Hamdy; Safinaz Megahed; Dina Y. Elalfy (BMC, 2024)
Abstract Background Using Zonulin and Copeptin as potential obesity markers in children, hasn't yet been focused. Aim To evaluate the association between serum levels of both Zonulin and Copeptin with the obesity markers, and to assess their role as metabolic disturbance predictors in obese children. Methods A case-control study comprised 111 Egyptian children (45 males and 66 females); aged 6-10 years to avoid the effect of puberty (prepubertal). They were classified according to their body mass index (BMI) percentiles into: 72 obese (BMI ≥ 95th ), and 39 control ones (BMI > 15th - <85th ), based on the Egyptian Growth Charts for children and adolescents. Anthropometric parameters and blood pressure were measured, and body composition analysis, lipid profile, Zonulin, and Copeptin levels were assessed. Results The obese group showed a significantly higher value of Copeptin and a lower value of Zonulin than the control one Also, the obese group showed significant negative correlations between Zonulin and both anthropometric obesity markers and body composition, whereas Copeptin showed significant positive ones. Moreover, significant positive correlations were found between Copeptin and both body weight and fat distribution. Insignificant correlations were observed between both serum Zonulin and Copeptin levels and blood pressure and lipid profile. Conclusion Zonulin and Copeptin cannot be used as metabolic disturbance predictors, among Egyptian children, as they were insignificantly correlated with lipid profile or blood pressure.